2021
DOI: 10.7717/peerj.12253
|View full text |Cite
|
Sign up to set email alerts
|

UBE2E3 regulates cellular senescence and osteogenic differentiation of BMSCs during aging

Abstract: Background Osteoporosis has gradually become a public health problem in the world. However, the exact molecular mechanism of osteoporosis still remains unclear. Senescence and osteogenic differentiation inhibition of bone marrow mesenchymal stem cells (BMSCs ) are supposed to play an important part in osteoporosis. Methods We used two gene expression profiles (GSE35956 and GSE35958) associated with osteoporosis and selected the promising ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Mechanisms underlying senescent induced changes in MSCs have since then been addressed in multiple studies, identifying important mediators of MSC senescence [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. For instance, several miRNAs have been identified that are involved in regulating senescence and the balance between osteoblastic and adipocytic differentiation of BMSCs [ 52 , 55 , 60 , 61 ].…”
Section: Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms underlying senescent induced changes in MSCs have since then been addressed in multiple studies, identifying important mediators of MSC senescence [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. For instance, several miRNAs have been identified that are involved in regulating senescence and the balance between osteoblastic and adipocytic differentiation of BMSCs [ 52 , 55 , 60 , 61 ].…”
Section: Cellular Senescencementioning
confidence: 99%
“…Ubiquitin-conjugating enzyme E2E3 ( UB3E2E3 ) in vitro knock-down in young BMSCs accelerated cellular senescence and inhibited osteogenic differentiation [ 58 ]. In addition, knockdown of Bmi-1 , an important epigenetic regulator of stem cell self-renewal, leads to cellular senescence in young MSCs and overexpression to rejuvenation of old MSCs.…”
Section: Cellular Senescencementioning
confidence: 99%
“…Moreover, Mulan E3 ubiquitin ligase and UBE2E3 formed Mulan–Ube2e3 complexes, which then recruited GABARAP (GABAA receptor-associated protein) to participate in the process of mitosis [ 49 ]. Studies have found that UBE2E3 regulated cellular senescence in bone marrow mesenchymal stem cells (BMSCs) during aging and that this regulatory effect was achieved by modulating the function of the nuclear factor erythroid 2-related factor (Nrf2) [ 50 ]. Indeed, another study found that UBE2E3, together with its nuclear import receptor importin 11 (Imp-11), regulated Nrf2 distribution and activity in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described ( Liu et al, 2021b ; Peng et al, 2019 ). Total cell proteins were separated by SDS-PAGE and blotted on PVDF membranes (Millipore, Sigma, Burlington, MA).…”
Section: Methodsmentioning
confidence: 99%